Video-Assisted Mini-Open Sublay (VAMOS): A Simple Hybrid Approach for Lateral Incisional Hernias - Schwab, Robert; Sahm, Joachim; Willms, Arnulf Gregor (Frontiers in Surgery, 2018)
Purpose The purpose is to present a new hybrid approach of lateral incisional hernia repair associated with reduced operative trauma and anatomically optimal mesh placement. Methods Video-Assisted Mini-Open Sublay (VAMOS) consists of a laparoscopic atraumatic dissection of the hernia sac, diaphanoscopy, laparoscopically-assisted closure of the fascial gap and mesh placement in sublay position through a minimized skin incision. Feasibility of this concept was assessed in a cohort of 7 consecutive patients. Results VAMOS approach was feasible in all 7 patients. Median hernia size was 8 cm, the median skin incision width was 7.7 cm. Median operative time was 86 min. In all patients a mesh overlap of at least 3 cm on all sides of the fascial gap was ensured. On short-term follow-up no procedure related complications were recorded, seroma formation occurred in 2 patients. Pain medication was necessary for median 4.9 days. There was no need for pain medication on day 14, whatsoever. Conclusion Initial VAMOS results show that the technique is simple, time-saving and safe. It provides a significant reduction in postoperative pain. Through implantation in the intermuscular sublay position and minor access-related trauma, it is possible to achieve a biomechanically optimal mesh position, to lay the foundations for sufficient remodelling of the abdominal wall, and to prevent recurrence as well as local complications. All in all, VAMOS appears to have several advantages over current surgical strategies.